Human dissemination of genes and microorganisms in Earth's Critical Zone - Yong‐Guan Zhu; Michael Gillings; Pascal Simonet; Dov Stekel; Steven Banwart; Josep Penuelas (Global Change Biology, 2018)
Earth's Critical Zone sustains terrestrial life and consists of the thin planetary surface layer between unaltered rock and the atmospheric boundary. Within this zone, flows of energy and materials are mediated by physical processes and by the actions of diverse organisms. Human activities significantly influence these physical and biological processes, affecting the atmosphere, shallow lithosphere, hydrosphere, and biosphere. The role of organisms includes an additional class of biogeochemical cycling, this being the flow and transformation of genetic information. This is particularly the case for the microorganisms that govern carbon and nitrogen cycling. These biological processes are mediated by the expression of functional genes and their translation into enzymes that catalyze geochemical reactions. Understanding human effects on microbial activity, fitness and distribution is an important component of Critical Zone science, but is highly challenging to investigate across the enormous physical scales of impact ranging from individual organisms to the planet. One arena where this might be tractable is by studying the dynamics and dissemination of genes for antibiotic resistance and the organisms that carry such genes. Here we explore the transport and transformation of microbial genes and cells through Earth's Critical Zone. We do so by examining the origins and rise of antibiotic resistance genes, their subsequent dissemination, and the ongoing colonization of diverse ecosystems by resistant organisms.

The soil resistome: a critical review on antibiotic resistance origins, ecology and dissemination potential in telluric bacteria - Joseph Nesme; Pascal Simonet (Environmental Microbiology, 2015)
Summary Soil is a large reservoir of microbial diversity and the majority of antimicrobial compounds used today in human and veterinary health care have been isolated from soil microorganisms. The D arwinian hypothesis of an ‘arms‐shields race’ between antibiotic producers and resistant strains is often cited to explain antibiotic resistance gene determinants ( ARGD ) origins and diversity. ARGD abundance and antibiotic molecule exposure are, however, not systematically linked, and many other factors can contribute to resistance gene emergence, selection and dissemination in the environment. Soil is a heterogeneous habitat and represents a broad spectrum of different ecological niches. Soil harbours a large genetic diversity at small spatial scale, favouring exchange of genetic materials by means of horizontal gene transfer ( HGT ) that will contribute to ARGD dissemination between bacteria and eventually acquisition by pathogen genomes, therefore threatening antibiotic therapies. Our current knowledge on the extent of the soil resistome abundance and diversity has been greatly enhanced since the metagenomic revolution and help of high‐throughput sequencing technologies. Different ecological hypotheses explaining their high prevalence in soil and questioning their transfer rate to pathogens, in respect to these recent experimental results, will be discussed in the present review.

Microbial community development and unseen diversity recovery in inoculated sterile soil - Tom O. Delmont; Davide Francioli; Sophie Jacquesson; Sandra Laoudi; Alban Mathieu; Joseph Nesme; Maria Teresa Ceccherini; Paolo Nannipieri; Pascal Simonet; Timothy M. Vogel (Biology and Fertility of Soils, 2014)

Soil microbial diversity: an ISO standard for soil DNA extraction - Laurent Philippot; Cristina Abbate; Antonio Bispo; Thierry Chesnot; Sara Hallin; Philippe Lemanceau; Kristina Lindström; Pascal Pandard; Esperanza Romero; Michael Schloter; Pascal Simonet; Kornelia Smalla; et al. (Journal of Soils and Sediments, 2010)

Molecular tools in rhizosphere microbiology—from single-cell to whole-community analysis - Jan Sørensen; Mette Haubjerg Nicolaisen; Eliora Ron; Pascal Simonet (Plant and Soil, 2009)

Development and validation of a prototype 16S rRNA‐based taxonomic microarray for Alphaproteobacteria - Hervé Sanguin; Aude Herrera; Christine Oger‐Desfeux; Arnaud Dechesne; Pascal Simonet; Elisabeth Navarro; Timothy M. Vogel; Yvan Moënne‐Loccoz; Xavier Nesme; Geneviève L. Grundmann (Environmental Microbiology, 2006)
Summary The microarray approach has been proposed for high throughput analysis of the microbial community by providing snapshots of the microbial diversity under different environmental conditions. For this purpose, a prototype of a 16S rRNA‐based taxonomic microarray was developed and evaluated for assessing bacterial community diversity. The prototype microarray is composed of 122 probes that target bacteria at various taxonomic levels from phyla to species (mostly Alphaproteobacteria ). The prototype microarray was first validated using bacteria in pure culture. Differences in the sequences of probes and potential target DNAs were quantified as weighted mismatches (WMM) in order to evaluate hybridization reliability. As a general feature, probes having a WMM > 2 with target DNA displayed only 2.8% false positives. The prototype microarray was subsequently tested with an environmental sample, which consisted of an Agrobacterium ‐related polymerase chain reaction amplicon from a maize rhizosphere bacterial community. Microarray results were compared to results obtained by cloning‐sequencing with the same DNA. Microarray analysis enabled the detection of all 16S rRNA gene sequences found by cloning‐sequencing. Sequences representing only 1.7% of the clone library were detected. In conclusion, this prototype 16S rRNA‐based taxonomic microarray appears to be a promising tool for the analysis of Alphaproteobacteria in complex ecosystems.

Type I Polyketide Synthases May Have Evolved Through Horizontal Gene Transfer - Aurélien Ginolhac; Cyrille Jarrin; Patrick Robe; Guy Perrière; Timothy M. Vogel; Pascal Simonet; Renaud Nalin (Journal of Molecular Evolution, 2005)

Quantification of bacterial subgroups in soil: comparison of DNA extracted directly from soil or from cells previously released by density gradient centrifugation - Sophie Courtois; Åsa Frostegård; Pernilla Göransson; Geraldine Depret; Pascale Jeannin; Pascal Simonet (Environmental Microbiology, 2001)
All molecular analyses of soil bacterial diversity are based on the extraction of a representative fraction of cellular DNA. Methods of DNA extraction for this purpose are divided into two categories: those in which cells are lysed within the soil (direct extraction) and those in which cells are first removed from soil (cell extraction) and then lysed. The purpose of this study was to compare a method of direct extraction with a method in which cells were first separated from the soil matrix by Nycodenz gradient centrifugation in order to evaluate the effect of these different approaches on the analysis of the spectrum of diversity in a microbial community. We used a method based on polymerase chain reaction (PCR) amplification of a 16S rRNA gene fragment, followed by hybridization of the amplified fragments to a set of specific probes to assess the phylogenetic diversity of our samples. Control parameters, such as the relationship between amount of DNA template and amount of PCR product and the influence of competing DNA on PCR amplification, were first examined. Comparison between extraction methods showed that less DNA was extracted when cells were first separated from the soil matrix (0.4 µg g −1 dry weight soil versus 38–93 µg g −1 obtained by in situ lysis methods). However, with the exception of the γ‐subclass of Proteobacteria, there was no significant difference in the spectrum of diversity resulting from the two extraction strategies.

Co‐evolution between Frankia populations and host plants in the family Casuarinaceae and consequent patterns of global dispersal - Pascal Simonet; Elisabeth Navarro; Carole Rouvier; Paul Reddell; Jeff Zimpfer; Yvon Dommergues; René Bardin; Pilar Combarro; Jérôme Hamelin; Anne‐Marie Domenach; François Gourbière; Yves Prin; et al. (Environmental Microbiology, 1999)
Symbioses between the root nodule‐forming, nitrogen‐fixing actinomycete Frankia and its angiospermous host plants are important in the nitrogen economies of numerous terrestrial ecosystems. Molecular characterization of Frankia strains using polymerase chain reaction/restriction fragment length polymorphism (PCR/RFLP) analyses of the 16S rRNA‐ITS gene and of the nif D– nif K spacer was conducted directly on root nodules collected worldwide from Casuarina and Allocasuarina trees. In their native habitats in Australia, host species contained seven distinctive sets of Frankia in seven different molecular phylogenetic groups. Where Casuarina and Allocasuarina trees are newly planted outside Australia, they do not normally nodulate unless Frankia is introduced with the host seedling. Nodules from Casuarina trees introduced outside Australia over the last two centuries were found to contain Frankia from only one of the seven phylogenetic groups associated with the host genus Casuarina in Australia. The phylogenetic group of Frankia found in Casuarina and Allocasuarina trees introduced outside Australia is the only group that has yielded isolates in pure culture, suggesting a greater ability to survive independently of a host. Furthermore, the Frankia species in this group are able to nodulate a wider range of host species than those in the other six groups. In baiting studies, Casuarina spp. are compatible with more Frankia microsymbiont groups than Allocasuarina host spp. adapted to drier soil conditions, and C. equisetifolia has broader microsymbiont compatibility than other Casuarina spp. Some Frankia associated with the nodular rhizosphere and rhizoplan, but not with the nodular tissue, of Australian hosts were able to nodulate cosmopolitan Myrica plants that have broad microsymbiont compatibility and, hence, are a potential host of Casuarinaceae‐infective Frankia outside the hosts' native range. The results are consistent with the idea that Frankia symbiotic promiscuity and ease of isolation on organic substrates, suggesting saprophytic potential, are associated with increased microsymbiont ability to disperse and adapt to diverse new environments, and that both genetics and environment determine a host's nodular microsymbiont.

A review of available systems to investigate transfer of DNA to indigenous soil bacteria - Sylvie Clerc; Pascal Simonet (Antonie van Leeuwenhoek, 1998)

Characterization of natural populations of Nitrobacter spp. using PCR/RFLP analysis of the ribosomal intergenic spacer - Elisabeth Navarro; Pascal Simonet; Philippe Normand; René Bardin (Archives of Microbiology, 1992)